Upaya Pencegahan Komplikasi Kehamilan Dengan Deteksi Dini Preeklamsia - Siti Komariyah; Apriani Kartini Tanggu; Delsiana Holo; Jusni (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2024)
Pregnancy is an important phase in a woman's life, but it is not uncommon for pregnancies to experience various complications that can harm the mother and fetus. One way to prevent this complication is through early detection of preeclampsia. Preeclampsia is one of the direct causes of death in pregnant women. The number of maternal deaths in Kediri City in 2023 was 24 cases with the highest total causes of death caused by bleeding, high blood pressure and other triggers. One of the early detection of pre-eclampsia in pregnant women is by calculating BMI and checking urine protein. The aim of this activity is to prevent pregnancy complications by early detection of preeclampsia. Community service was carried out from July 15 to August 3 2024 in Rejomulyo Village and the target of this activity was 20 pregnant women. Using preparation, implementation and evaluation methods for BMI examination by measuring BB/TB and urine protein using a dipstick. The results of the service were 4 (20%) pregnant women who were obese and 1 (5%) pregnant women who were overweight and 3 (15%) pregnant women with urine protein results (+). Thus, early detection High risk pregnancy is very important to reduce maternal and fetal morbidity and mortality rates by preventing pregnancy complications.